Bone loss and wrist fractures after withdrawal of hormone therapy: The 15-year follow-up of the OSTPRE cohort. (March 2016) - Saarelainen, Jarmo; Hassi, Saara; Honkanen, Risto; Koivumaa-Honkanen, Heli; Sirola, Joonas; Kröger, Heikki; Komulainen, Marja H.; Tuppurainen, Marjo
Highlights: Long-term HT-use protects from bone loss and wrist fracture, reducing, thus, the incidence of osteopenia and osteoporosis. HT-use of less than 5 years does not have long-term bone protection. The three main reasons for discontinuation of HT were resolution of menopausal symptoms, disease and fear of adverse effects or cancer. Abstract: Context: Long-term bone mineral density (BMD) or fracture incidence changes after withdrawal of postmenopausal hormone therapy (HT) are not well known. Objective: To study long-term postmenopausal bone loss and incidence of wrist fracture in respect to duration and withdrawal of self-reported HT. Design/setting: A 15-year follow-up of the population-based prospective OSTPRE cohort in Kuopio, Finland. Participants: Women (mean baseline age 53.4 years, range 48.1–59.6) were divided into four groups based on duration of HT: (1) never users (non-HT); (2) those who had used HT only throughout the 1st 5-year period (HT5); (3) throughout the first 10-years (HT10); (4) those who used HT throughout the entire 15-year follow-up (HT15). Outcome measures: Femoral ( n  = 857) and spinal ( n  = 599) BMD measurements with dual X-ray absorptiometry (DXA) were carried out at 5-year intervals in 1989–2004. Wrist fracture incidence in 1989–2004 was studied in a population of 5119 women. Results: The adjustedspinal BMD (L2–L4) changes by HT use during the entire 15-year follow-up were −4.8% for non-HT ( p  < 0.0001), −4.2% for HT5 ( p  = 0.003), +0.02% for HT10 ( p  > 0.05) and +3.2% for HT15 ( p  < 0.0001) groups. The respectivefemoral bone losses were -8.6% for non-HT ( p  < 0.0001), −7.9% for HT5 ( p  < 0.0001), −2.5% for HT10 ( p  = 0.010) and −0.2% for HT15 ( p  > 0.05) groups. Comparing to non-HT group the risk ofwrist fracture was reduced by 33% ( p  = 0.045) in HT10 group and by 63% ( p  < 0.0001) in HT15 group during the 15-year follow-up. Conclusion: Long-term HT-use protects from bone loss. Thus, it reduces the incidence of osteopenia, osteoporosis and wrist fractures. Still, HT-use of less than 5 years did not have long-term bone protective effects, but a larger sample size is needed to confirm this result.